2023
DOI: 10.3389/fmicb.2023.1217617
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles with plasma-polymerized hexamethyldisiloxane coating on 3D printed substrates are non-cytotoxic and effective against respiratory pathogens

Anna Machková,
Eva Vaňková,
Klára Obrová
et al.

Abstract: Due to the emerging resistance of microorganisms and viruses to conventional treatments, the importance of self-disinfecting materials is highly increasing. Such materials could be silver or its nanoparticles (AgNPs), both of which have been studied for their antimicrobial effect. In this study, we compared the biological effects of AgNP coatings with and without a plasma-polymerized hexamethyldisiloxane (ppHMDSO) protective film to smooth silver or copper coatings under three ambient conditions that mimic the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Similarly, it was shown that a plasma-polymerized siloxane layer could improve the performance of silver nano-particles on a medical device. The thin (16 nm) layer maintained the antimicrobial properties of the nano-particles while improving the biocompatibility [46]. Plasma processing also offers a number of applications in the control of drug release.…”
Section: Deposition Of Antimicrobial Filmsmentioning
confidence: 99%
“…Similarly, it was shown that a plasma-polymerized siloxane layer could improve the performance of silver nano-particles on a medical device. The thin (16 nm) layer maintained the antimicrobial properties of the nano-particles while improving the biocompatibility [46]. Plasma processing also offers a number of applications in the control of drug release.…”
Section: Deposition Of Antimicrobial Filmsmentioning
confidence: 99%